Progressive Islam: Examining the Differences and Synergies Between Islam Nusantara and Progressive Islam - Ritonga, Raja; Mahmoud Ali Rababah (MADINAH, 2025)
Islam Nusantara, rooted in Indonesia's local traditions and culture, offers a moderate and inclusive approach to Islam, emphasizing social harmony and interfaith tolerance. Meanwhile, Islam Berkemajuan, often associated with the Muhammadiyah movement, focuses on modernization, rationality, and social progress through education and community development. This study aims to explore and analyze the differences and potential synergies between the concepts of Islam Nusantara and Islam Berkemajuan. The method used is a literature review with content analysis. The study data is derived from various books, articles, and other scholarly works relevant to the study's theme. The findings indicate that Islam Nusantara and Islam Berkemajuan are two complementary concepts that can create a harmonious and progressive society. By examining the theological, historical, and sociological foundations of these two concepts, the study provides deep insights into their contributions to the development of Islam in Indonesia in integrating traditional values with the demands of modern progress.